1974
DOI: 10.1042/cs048161s
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis and Prevention of Stroke in Spontaneously Hypertensive Rats

Abstract: 1.A colony of stroke-prone spontaneously hypertensive rats has been developed by selective breeding.2. These animals developed severe hypertension early in life, the magnitude of the hypertension being closely related to the incidence of stroke.3. No evidence was obtained of any humoral factor responsible for strokes.4. Local factors predisposing to stroke were a scanty arterial supply with characteristic recurrent branching of long and large arteries, together with increased vascular permeability, angio-necro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
92
0

Year Published

1992
1992
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(94 citation statements)
references
References 0 publications
2
92
0
Order By: Relevance
“…This left 95 studies (Set 5). A second Medline search was performed (9 November 2007) and 3 additional papers retrieved (Nishimura et al, 2006;Jesmin et al, 2007;Nishimura et al, 2007) giving a total of 98 studies (Set 6), the earliest from 1975 (Okamoto et al, 1975). A further three papers have been added in the final version of the manuscript (total = 101).…”
Section: Methodsmentioning
confidence: 99%
“…This left 95 studies (Set 5). A second Medline search was performed (9 November 2007) and 3 additional papers retrieved (Nishimura et al, 2006;Jesmin et al, 2007;Nishimura et al, 2007) giving a total of 98 studies (Set 6), the earliest from 1975 (Okamoto et al, 1975). A further three papers have been added in the final version of the manuscript (total = 101).…”
Section: Methodsmentioning
confidence: 99%
“…11) Spontaneously hypertensive rat stroke-prone (SHRSP) is a widely used animal model for hypertension and stroke. 12) Iritani et al reported that the serum cholesterol level in SHRSP was low when compared with that in normotensive age-matched Wistar Kyoto rats (WKY). 13) We previously reported that the low serum cholesterol level in SHRSP as compared with WKY may be attributable to the reduced activity of MPD and not 3-hydroxy-3-methylglutaryl coenzyme A (HMG-CoA) reductase.…”
Section: )mentioning
confidence: 99%
“…11,12) SHRSP has a lower serum cholesterol level than the normotensive Wistar Kyoto rat (WKY). 13) We previously indicated that the lower activity of MPD caused by the reduced amount of this enzyme was responsible for the reduced cholesterol biosynthesis in the liver of SHRSP.…”
mentioning
confidence: 99%